Testing the risk compensation hypothesis for safety helmets in alpine skiing and snowboarding. Issue 3 (13th June 2007) - Scott, Michael D; Buller, David B; Andersen, Peter A; Walkosz, Barbara J; Voeks, Jennifer H; Dignan, Mark B; Cutter, Gary R
Abstract : Objective: The prevalence of helmet use by alpine skiers and snowboarders was estimated and self-reports on risk taking were assessed to test for potential risk compensation when using helmets in these sports. Setting: Skiers and snowboarders were observed and interviewed at 34 resorts in the western United States and Canada. Subjects: Respondents were 1779 adult skiers and snowboarders in the 2003 ski season. Outcome measures: Observations of helmet use and questions about perceived speed and degree of challenge when not wearing a helmet (helmet wearers) or in previous ski seasons (non-helmet wearers). Results: Helmet wearers reported that they skied/snowboarded at slower speeds (OR = 0.64, p<0.05) and challenged themselves less (OR = 0.76, p<0.05) than non-helmet wearers. Adoption of safety helmets in 2003 (23%) continued to increase over 2002 (OR = 0.46, p<0.05) and 2001 (OR = 0.84, p<0.05). Conclusions: No evidence of risk compensation among helmet wearers was found. Decisions to wear helmets may be part of a risk reduction orientation. Helmet use continues to trend upwards but adoption may be slowing.